Impact of financial liberalisation on income inequality: A PVAR approach - Chokri Zehri (Economics and Econometrics Research Institute (EERI), 2019)
I estimate a panel vector autoregressive model (PVAR) to study the impact of financial liberalisation on income inequality. The analysis is carried out for 162 countries over the period 1980-2015. The results show that capital account liberalisation and financial development increase inequality. However, it change according to the category of income countries (low, middle and high-income) and according to the period of study used (before and after 1990). The shocks caused by the indicators of financial liberalisation on income inequality are very low but persistent in time.
Keywords: F38; F41; F02; 330; financial liberalization; income; inequality; PVAR